Social Gaps in Eligibility for a Matriculation Certificate in Israel: A Pre- and Post-COVID-19 Comparison. - Addi-Raccah, Audrey; Streisfeld, Shani (Social Justice Research, 2025)
The COVID-19 pandemic, as a global health crisis, has disrupted schools and students' lives, and raised concern about an increase in social inequality. Three hypotheses were examined: 1. Between pre-COVID-19, during COVID-19, and post-COVID-19, there will be a decrease over time in the percentage of matriculation certificate (PMC) and outstanding matriculation certificate eligibility (POMC) in schools; (H2) The decrease in PMC over time will be greater in schools in the Arab sector compared to those in the Jewish sector and within each educational sector, in low-socioeconomic schools compared to high-socioeconomic schools; (H3) Sectorial and socioeconomic differences in schools' POMC eligibility over time will be greater than the PMC eligibility. These hypotheses were tested within the context of the Ministry of Education modification of the format of matriculation exams, at 12th grade. The data included 863 schools in the Jewish and Arab sectors on four time points: pre (2019), during (2020-2021), and post-COVID-19 (2022). Descriptive analysis and a two-level linear mixed model with repeated measures were conducted. An increase in the percentage of matriculation certificate eligibility was found in schools, particularly in disadvantaged ones, reducing sectoral and socioeconomic inequality. At the same time there was an increase in the percentage of outstanding matriculation certificates, mainly among advantaged schools, leading to an increase in inequality. The findings indicate a decrease in vertical stratification and an increase in horizontal stratification, emphasizing the complexity of promoting educational opportunities in the era of risk society.